Grading and Size Classification of Chicken Eggs Produced by Native, Egg-Type, Meat-Type, Dual-Purpose and Fancy-Type Breeds Under Philippine Conditions - Bondoc , O.L.; Santiago, R.C.; Bustos, A.R.; Ebron, A.O.; Ramos, A.R. (International Journal of Poultry Science, 2021)
Background and Objective: The egg grading and size classification system used for commercial chicken breeds and hybrids is proposed for Philippine native chickens. In this regard, this study aimed to compare the egg characteristics of native breeds to egg-type, meat-type, dual-purpose and fancy-type breeds. Materials and Methods: A total of 315 eggs from 14 chicken breeds was used in this study. The size, shape, internal and external egg quality characteristics were analyzed. Egg parameters were analyzed by least square procedures to account for the effects of breed, size, grade classification and hen age. Results: Egg weight was highly correlated (p0.05) to Haugh Unit. According to the size classification system the eggs were 4.1% jumbo, 7.3% extra-large, 20.3% large, 21.9% medium, 39.7% small and 6.7% peewee. Egg distribution by grade classification based on Haugh Unit was 13.3% Grade AA, 40.6% Grade A, 43.2% Grade B and 2.9% Grade C. Conclusion: Philippine native chickens (Banabang Kalabaw, Joloano, Paraoakan and Palawan Lasak), Black Silkies and White Silkies eggs were classified as small, while White Rock eggs were classified as medium. Black Australorp, Barred Plymouth Rock, New Hampshire, Rhode Island Red and Taiwan Yellow eggs were classified as large. Nagoya and White Leghorn eggs were classified as extra-large. The Philippine native chickens, Barred Plymouth Rock, New Hampshire, Taiwan Yellow and White Leghorn eggs were classified as Grade A. Eggs from White Rock, Black Silkies, White Silkies, Black Australorp, Nagoya and Rhode Island Red were classified as Grade B.